Building builders: entrepreneurship education from an ecosystem perspective at MIT - Artur Tavares Vilas Boas Ribeiro; Juliana Natsumi Uechi; Guilherme Ary Plonski (Triple Helix, 2018)
This study is about new possibilities on entrepreneurship education. With the emergence of the entrepreneurial universities, academics and university managers started to pay more attention to fostering entrepreneurship among students. However, entrepreneurship education research became more oriented towards teacher activities and neglected the entrepreneurship ecosystem around the university and its role in educating an entrepreneur. This article aims to present new possibilities for entrepreneurship education from this ecosystem perspective. The method was a case study of Massachusetts Institute of Technology, and the results show educational practices that go beyond the classical model of classrooms, involving student-led activities, mentorship programs, competitions, and others. Project-based courses, experience-based activities and active-based activities are well covered in the data presented. In the discussions, we also present a model of organizing entrepreneurship education efforts and compare our results with other research on Swedish entrepreneurial universities. The conclusion reinforces the need to see entrepreneurship education through the lens of ecosystems, highlighting opportunities for future studies.
Keywords: 330; Entrepreneurial universities; University; Entrepreneurship; Entrepreneurial ecosystems; Entrepreneurship education; Education; Innovation; Entrepreneurial culture; Spin-offs; Venture creation; MIT; Massachusetts Institute of Technology